CHALLENGES FACED BY THE CONSTRUCTION INDUSTRIES IN INDIA - Akshay D. Karnavat; Ismail Janab; Pujan Shah (International Journal of Innovations in Engineering Research and Technology, 2021)
The construction industries in Indiain past few decades have faced the several issues. Being the second largest contributor to the GDP the sector has lot of expectation. The stakeholder of the sector areexpecting the sector to provide the excellent projects at the minimum cost at the same time the labours and the material cost is not in the control of the industry. The construction industry is going through the multiple challenges where the skills of the labours are to be enhanced; the technology to be improved, cost must be controlled and the quality to be improved. The enrichment in any one of the factor stated above has several concerns associated with it. Authors have offered the overview of the problems faced by the Indian construction industries in this manuscript.